Competitive intelligence and decision problems - David, Amos. (London : Wiley, 2013)
The development of a research, teaching, or application of competitive (economic) intelligence requires a strategic and transverse vision in regards to related issues. It is essential to integrate the role of culture when interpreting results, either from the training of a specialist or in respect to a country or region. The authors of this book, members of an expert group supported by the CNRS in France, bring all of their talents together to create a comprehensive book that does just this and more.
Chapter 5. Study of Risk Factors in Competitive Intelligence Decision Making: A Cognitive Approach5.1. Decision making and decision problems; 5.1.1. Introduction; 5.1.2. Fundamental aspects of the decision problem; 5.1.3. Decision and cognitive capacity; 5.1.4. Decisions in the context of CI; 5.2. Risks and RFs in CI; 5.2.1. Introduction; 5.2.2. Actors and their interactions in CI; 5.2.3. Risks and RFs; 5.3. Cognitive capacity, a risk, and decision factor; 5.3.1. Introduction; 5.3.2. Cognitive capacity and its effects on decision making; 5.3.3. Cognitive model of RFs; 5.4. Conclusion.
5.5. Bibliography.
Includes bibliographical references.
Print version record.
Keywords: Business intelligence; Decision making; Business intelligence; Decision making; Electronic books